Ordering the city : land use, policing, and the restoration of urban America - Garnett, Nicole Stelle (Yale University Press, 2010)
This work highlights the multiple, often overlooked, and frequently misunderstood connections between land use and development policies and policing practices. In order to do so the book draws upon multiple literatures as well as concrete case studies to better explore how these policy arenas intersect and conflict.